The Effect of Interactive Learning Media on Students' Understanding of Basic Mathematical Concepts in SDN 1 Tebaban - Adawiyah, Siti Rabiatul; Maritasari, Donna Boedi; Yazid, Muh (IJE : Interdisciplinary Journal of Education, 2024)
This study aims to determine the effect of the use of interactive learning media (wordwall) on the understanding of basic mathematical concepts of grade IV students at SDN 1 Tebaban. This type of research is a quantitative research of experimental methods with  a quasi-experimental design of  pretest-posttest control group design. The population of this study is class IV A and IV B which totals 35 students. The sample of this study uses a saturated sampling technique. The data collection technique in this study uses observation sheets, questionnaire sheets and pretest and posttest test sheets. The data analysis techniques in this study include observation and questionnaire data analysis, descriptive analysis, normality test, variance homogeneity test and independent samples test. The results of the observation sheet showed that the students' understanding of basic mathematical concepts in the experimental class reached 75% ('Very Good'), higher than the control class which only reached 62.99% ('Good'). Based on the results of the questionnaire, the use of wordwall interactive media  was proven to be more effective in improving students' understanding than mind mapping learning media and teaching aids in the control class, with 91% of students in the experimental class supporting the use of wordwalls, compared to 80% in the control class. The t-test showed a value of Sig. (2-tailed) 0.02, so that the alternative hypothesis was accepted, indicating a significant influence of interactive learning media on the understanding of mathematical concepts of grade IV students at SDN 1 Tebaban.